The acute effects of joint manipulative techniques on markers of autonomic nervous system activity: a systematic review and meta-analysis of randomized sham-controlled trials - Picchiottino, Mathieu (Chiropr Man Therap, 2019)
BACKGROUND: The autonomic nervous system (ANS) interests many chiropractors and manual therapists, because joint manipulative techniques (JMT), e.g. high velocity low amplitude (HVLA) manipulations and mobilizations, appear to produce acute changes in ANS mediated physiology. The complexity of this issue justifies a systematic critical literature review. OBJECTIVE: To review the literature comparing the acute changes in markers of ANS activity between JMT applied on spinal or peripheral joints and a sham procedure in healthy or symptomatic subjects. METHOD: We searched PsycINFO, PEDro, PubMed, Cochrane library, EMBASE, and Medline up to December 2017. We updated the search with PubMed, Cochrane library, EMBASE, and Medline including July 2018. Inclusion criteria were: randomized sham-controlled trials assessing the effect of JMT on markers of ANS activity; manually applied JMT, regardless of technique, applied on either healthy or symptomatic humans; outcome measurements recorded at baseline and repeated during and/or after interventions. Selection of articles and data extraction were performed independently by two reviewers. The quality of studies was assessed using the Cochrane ‘risk of bias’ tool and a technical check-list. Results were reported narratively with some meta-analyses. The Cochrane GRADE approach was used to assess the certainty of evidence. RESULTS: Twenty-nine of 2267 studies were included in the synthesis. Mobilizations (oscillatory technique) probably produce an immediate and short-term, bilateral increase in skin sympathetic nerve activity (reflected by an increase in skin conductance) regardless of the area treated (moderate-certainty evidence). It is uncertain whether the sympathetic arousal also explains an increase in respiratory rate (very low-certainty evidence). Our evaluation of the literature suggests that spinal sustained apophyseal glides (SNAGs) mobilization and HVLA manipulation of the spine may have no acute effect on the studied markers of ANS activity (very low- to low-certainty evidence). CONCLUSION: Some types of mobilizations probably produce an immediate and short-term, statistically significant increase in skin sympathetic nerve activity when compared to a sham procedure, whereas spinal SNAGs and spinal HVLA techniques may have no acute effect on the studied markers of ANS activity. No region-specific results were noted. The literature suffers from several shortcomings, for which reason we strongly suggest further research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12998-019-0235-1) contains supplementary material, which is available to authorized users.